MINIMUM WAGE IMPLEMENTATION AND MANAGEMENT IN A POST-RECESSION ECONOMY: THE NIGERAN EXPERIENCE - Sulaiman, Atiku; Olanrewaju, Lawal Ibrahim; Tinuke, Fapohunda M. (European Scientific Journal, ESJ, 2012)
The practice of minimum wage has been on even before the First World War and it has been the subject of several serious discourses. The objective of minimum wage fixing is to give wage-earners the necessary social protection in terms of minimum permissible levels of wages.This examined strategies for the effective management and implementation of minimum wage in Nigeria. A brief literature on the nature and etymology of minimum wage and its determination criterion was highlighted. Issues and challenges to minimum wage implementation were.the labour market situation, level of unemployment and poverty; the unfriendly posture of some state governors on minimum wage; some organisations have a culture of unfair labour practices; unavailability of statistics, faulty criterion in fixing minimum wages; poor enforcement capacity ,the challenge of non-unionised workers, casualization and contract staff. The effective management and implementation of the minimum wage requires the efforts, commitment and collaboration of all stakeholders.The impact and usefulness of a minimum wage policy depends on whether minimum wages are paid.